2002
DOI: 10.1521/psyc.65.2.110.19930
|View full text |Cite
|
Sign up to set email alerts
|

Living with a Schizophrenic Patient: A Comparative Study of Burden as It Affects Parents and Spouses

Abstract: Based on the analysis of 42 in-depth interviews, this article highlights different aspects of the subjective burden experienced by parents and spouses of patients suffering from schizophrenia. The onset of a schizophrenic disorder and acute episodes during the later course of the disease lead to considerable emotional distress for the patients' caregivers. In everyday life with the patient, parents and spouses experience a comparatively less dramatic chronic burden, which nevertheless can severely affect their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
0
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 17 publications
6
66
0
11
Order By: Relevance
“…The reported moderate to severe level of burden among the study caregivers supports the earlier findings. Parents of schizophrenia patients having problems and worries regarding the parent-child relation are of importance, such as the question of possibly being responsible for the illness because of poor parenting, and the dilemma of a permanent, possibly lifelong dependency of the patient 15 . Family intimacy and conflict have been found to reflect the degree of burden or reward experienced and it is suggested that the family system, as the context within which the patient exists, is seen as the mediating environment for caregiving burden and reward 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The reported moderate to severe level of burden among the study caregivers supports the earlier findings. Parents of schizophrenia patients having problems and worries regarding the parent-child relation are of importance, such as the question of possibly being responsible for the illness because of poor parenting, and the dilemma of a permanent, possibly lifelong dependency of the patient 15 . Family intimacy and conflict have been found to reflect the degree of burden or reward experienced and it is suggested that the family system, as the context within which the patient exists, is seen as the mediating environment for caregiving burden and reward 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Esses resultados indicam que, de maneira geral, o papel de cuidador afetou os três grupos estudados de forma semelhante. Esses dados corroboram resultados encontrados por Jungbauer e Angermeyer 11 , que também encontraram algumas semelhanças na sobrecarga sentida por cônjuges e pais cuidadores, por exemplo, a variação da sobrecarga de acordo com a fase da doença do paciente.…”
Section: Discussionunclassified
“…Esses resultados corroboram dados encontrados na literatura, indicando que os pais, além de serem apontados como os principais cuidadores dos pacientes psiquiátricos, também são os que apresentam sobrecarga mais elevada 14,15,19,25 . Segundo Jungbauer e Angermeyer 11 , os cuidadores são confrontados com uma sobrecarga específi-ca, pautada pelo tipo de relacionamento que têm com o paciente. Nesse sentido, o grau de parentesco que o cuidador tem com o paciente determina as especificidades do relacionamento entre eles, resultando em diferenças específicas na sobrecarga.…”
Section: Discussionunclassified
See 2 more Smart Citations